Daya Hambat Perasan Daun Sambiloto Terhadap Pertumbuhan Bakteri Escherichia coli - SAWITTI, MADE YENDHI; MAHATMI, HAPSARI; BESUNG, NENGAH KERTA (Faculty of Veterinary Medicine, Udayana University, 2013)
The purpose of this study was to find out the ability of sambiloto extract to inhibit the growth of Escherichia coli (E. coli) in vitro. Escherichia coli ATCC 25922 was obtained from the Microbiology Laboratory of Medical Faculty, Udayana University and further used in this study. The ability of sambiloto extract leaves to inhibit E. coli bacteria ATCC 25922 was tested using modified Kirby-Bauer method. The experimental design used was complete random in the five treatments (sambiloto extract 0%, 25%, 50%, 75% and 100%, respectively) and four replications, and one positive control (oxytetracyclin). All data of inhibition zone were analysed using statistichial package SPSS 13 (Sampurna & Nindhia, 2009). This result showed that, sambiloto extract significantly inhibit the growth of E. coli (P<0,01). There was also a tendency diameter zone of inhibition increase as the concentration of sambiloto extract was increase (Y= 0.062 + 0.409K - 0.006K2 + 0.0000328K3) with correlation rate was 0,997.